INFLUENCE OF FORMULATION PARAMETERS ON TIZANIDINE HYDROCHLORIDE NANOPARTICLES - GUPTA RITU; BAJPAI MEENAKSHI (International Journal of Pharma and Bio Sciences, 2013)
Nanoparticulate drug delivery represents one of the frontier drug delivery that can provide controlled release and drug targeting. The aim of present study was to prepare nanoparticles of model drug tizanidine hydrochloride using double emulsion solvent diffusion method using different grades of Eudragit® and study the influence of drug & polymer on surface charge, influence of different polymer ratio on nanoparticle size, effect of different stabilizers on surface charge ,effect of stabilizer concentration, effect of polymer concentration ,effect of drug concentration, effect of internal to external phase volume (W1/O: W2) ratio on nanoparticle properties. FTIR Spectrum of optimized batch was compared with that of the pure drug. The thermal behaviour of prepared nanoparticles was studied by differential scanning calorimetry (DSC). The stability study of optimized batch was carried out at different storage conditions (5-8°C and 37 ± 1°C) for one month.